IoT-Based RFID System for Enhancing Kindergarten Student Safety : A Case Study - Masudia, Putri Elfa; Suekko, Febiola Kireya; Suharto, Nugroho (RIGGS: Journal of Artificial Intelligence and Digital Business, 2025)
Antonius Kindergarten is one of the kindergartens whose school building is a courtyard with a higher school level, namely SDK Santa Maria, and adjacent to the highway. One of the major safety concerns is the staircase leading to the second floor of the elementary school building, which connects directly to the hallway used by kindergarten students to access the bathroom This access point poses a significant risk, as kindergarten students often ascend the stairs unsupervised, resulting in injuries or crying without being noticed by teachers or staff. There is no guard because the staircase access is in the middle of the elementary school building. Based on this background, an automatic student security monitoring system is needed by utilizing technology, namely RFID (Radio Frequency Identification) and a website as a user interface. Based on the results of the RFID reading distance test using two models of tags, bracelets, and I.D. cards at 3 points of the area (gate, front door, stairwell) and 2 points of the height of the RFID reader (1.8 meters and 1.5 meters) the farthest distance of the RFID reader reading was obtained was 5 meters (I.D. card model rails area) and 3.5 meters (front door area bracelet model). The warning alarm for kindergarten admins sounds for 5 seconds repeatedly with a pause from the minimum reading distance of the RFID reader of 0.3 seconds. The farther away the Tag is from the reader, the longer the pause is.